Testing the weekend effect hypothesis: Time of day and lunar phase better predict the timing of births in laboratory‐housed primates than day of week. Issue 7 (9th July 2019) - Hopper, Lydia M.; Fernandez‐Duque, Eduardo; Williams, Lawrence E.
Abstract : The weekend effect hypothesis proposes that captive primates are more likely to give birth during times of low disturbance and reduced staff activity. The hypothesis specifically predicts that laboratory‐housed primates will be more likely to give birth during the weekend than weekdays when staff activity is reduced. To date, support for the weekend effect hypothesis has been mixed and based on studies with relatively few subjects. To further examine the hypothesis, we analyzed the birthing patterns of three genera of laboratory‐housed primates: squirrel monkeys ( Saimiri species, N = 2, 090 births), owl monkeys ( Aotus species, N = 479 births), and rhesus macaques ( Macaca mulatta, N = 2, 047 births). Contrary to predictions derived from the weekend effect hypothesis, the frequencies of births during weekends for all taxa were not significantly different from rates that would be expected by chance. However, while there was no variance across days of the week, all three taxa gave birth at nighttime, when staff was absent. This parallels reports of births in wild and captive monkeys, both diurnal and nocturnal, which are more likely to give birth during the night; plausibly a time when the environmental and social disturbance is lowest and the mother is safest to bond with her newborn infant. As all births occurred at night, we also explored the relationship between the lunar cycle and the timing of births timing. While the diurnal primates (i.e., Saimiri and Macaca ) were no more likely to give birth on "bright" nights than "dark" nights, owl monkeys ( Aotus ) had a much higher frequency of births on bright nights than darker ones, and at rates that deviated from chance. Our data provide a more detailed understanding on how the environment may influence captive monkey births but do not support the oft‐cited weekend effect hypothesis. Abstract : Research Highlights: For captive primates, time of day may be a more important predictor of parturition than day of week. Counter to the weekend effect hypothesis, for Aotus, Macaca, and Saimiri, birth timing was not influenced by day of the week. For nocturnal Aotus, lunar phase correlated with birth timing.